"Obedeciendo a la instrución de compendiar": registros de viagens de jesuítas nas cartas ânuas da província jesuítica do Paraguai (segunda metade do século XVII) - Fantin, Odair José (Universidade do Vale do Rio dos Sinos, 2010)
This dissertation aims to reconstruct the routes and the paths that were taken by Jesuit missionaries to the regions which were part of the Jesuit Province of Paraguay, from information that were extracted from Anuas Letters refer to the period between 1650 to 1675. This reconstruction will consider, in particular, the description that the missionaries made from the traveled distances, from the weather and the terrain conditions that they faced, from the vegetation that they found in the journeys, as well as from the necessary time and investments to come to their destinations and to satisfactory fulfillment their apostolic missions. It was theoretically based on Cultural History, we analysed the representations of the routes and the paths that were covered and inspired by the method of "literary geography" proposed by Franco Moretti, we compare the textual information with the mapping produced on the areas that were covered.
Keywords: Historia; Cartografia; Província jesuítica do Paraguai; Cartas ânuas; Jesuits; Cartography; Jesuit provice of Paraguay; Anuas letters; Jesuítas; ACCNPQ::Ciências Humanas::História